Extracts of Typhonium flagelliforme tubers for treatment of leukemia. - Abdul, Ahmad Bustamam; Mohan, Syam; Sukari, Mohd Aspollah; Abdul, Rashedee (2010)
The present invention relates to dichloromethane extracts of Typhonium flagelliforme tubers for use in the prophylaxis and/or treatment of leukemia, a pharmaceutical composition containing said extracts and a method of preparation of such extracts.